ENT 530 Social Media Portfolio: Therealperfume / Amira Ismail - Ismail, Amira (2021)
‘Real Perfume” is a local product originated from Batu Pahat, Johor, Malaysia under the company of GIFTBUZZ SDN BHD. It was founded by Noor Shahrene b. Hj Jumal and her co-founded is Azizah b Manan. Real Perfume is a sole proprietorship type of business that was established on 2015 with the motto of the company is "we help each other; we get a reward together". The company is located at Bangunan SBKK, Jalan Pegawai, 83300, Batu Pahat, Johor, Malaysia. Three people who work alongside Noor Shahrene b. Hj Jumal as Managing Director, which Azizah b Manan as Advisor, Nurul Niesa Administrative Manager, Siti Nadia as Financial Manager, and Nurul Natasya as Production Manager. Each of them has a background and qualification in entrepreneurship and business which enables them to share the knowledge and contribute it to the business flow and progress. Their expertise is to solve the problem of body odor & increase the self-confidence of consumers. Other than that, Real Perfume soothes the room with fragrance and they help all groups create the second income opportunity with a business of Real Perfume. They currently have 7 master stockiest, as well as an active master agent and dropship team of 230 people. Real Perfume begins with a 10ml travel pack, followed by a large 30 + 10ml pack (Combo pack) Real Perfume also introduced car perfumes in 2018 and the latest in Aromatherapy fragrances for living spaces that are suited for homes, rooms, workplaces, and more with additional unique benefits, based on its knowledge in the fragrance market and support from fans and users of Real Perfume. To promote the product, I developed and managed a Facebook page for "The Real Perfume" and worked as a drop shipper for them for almost a month. We aspire to reach our target market and provide the finest service possible.